The Directive Illocutionary Act Uttered by Ralph in “Wrack it Ralph 2” Movie - Rizki Noprian Thoni; Dhanu Ario Putra; Ami Pradana (Multidisciplinary Journals, 2026)
. Illocutionary acts are considered the core of the theory of speech acts. An illocutionary act is the action performed by the speaker in producing a given utterance This research was aimed to know the types of directive illocutionary act uttered by Ralph in “Wrack it Ralph 2” movie and to find out the messages that can be taken from the Ralph’s character. This research used a descriptive qualitative method. The data of this research was taken from Wreck it Ralph 2 movie. The movie also become the object of this research. The data in this research were the utterances spoken by Ralph character in the movie. the researcher only used two kinds of instruments; observation checklist and documentation. To know the directive illocutionary uttered by the subject of this research. This research used theory from Searle who divided the types of act into; asking, request, order, forbid, suggest, and warn based on Searle in Ismani and Effendi (2022) theory.  Moreover, to find out the messages that can be taken from the Ralph’s character the researcher used theory from Nurgiyantoro (2010). There were two findings of this research; (1) there were 100 directive illocutionary uttered by Ralph in the movie “Wrack it Ralph 2l”. The directive illocutionary were divided into forty nine direct utterances of asking, thirteen acts of request, ten acts of order, two acts of forbid, sixteen acts of suggest, and five acts of warn; (2) There were two kinds of messages from Ralph’s character, they were; Relationship between human beings and themselves (Self confidence, self esteem, bravery) and Relationship between human beings (friendship, loyalty, mutual help). Based on the conclusions above, the researcher would like to suggest further researchers who are interested in analyzing directive illocutionary in movies to learn more about the speect act analysis in a movie based on Searle or other experts.